2004
DOI: 10.1243/146442004323085554
|View full text |Cite
|
Sign up to set email alerts
|

Advanced bobsleigh design. Part 2: aerodynamic modifications to a two-man bobsleigh

Abstract: The aim of the present study is to improve the aerodynamic performance of the bobsled as a function of its shape and the relative position of the athletes inside the bobsled. This performance optimization problem is studied by means of wind tunnel testing. The aerodynamic responses of the manned and unmanned bobsleigh are analysed in terms of overall drag force measurements. Experimental results show that the proposed modi cations to the sidewalls and the nose section of the bobsled improve its drag performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Practical solutions to increase pressure inside the cavity, such as sidewall flaring or extending the arms of the brake person along the top of the cavity, have not proven to be effective. 50,64 The results of other studies have suggested that streamlining the bumpers or altering the front of the cowling by the addition of two rounded humps do not consistently reduce drag at race velocities. 62,64,66 Full-scale wind tunnel test results.…”
Section: Bobsleigh Aerodynamic Optimization Strategies Noted From the Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Practical solutions to increase pressure inside the cavity, such as sidewall flaring or extending the arms of the brake person along the top of the cavity, have not proven to be effective. 50,64 The results of other studies have suggested that streamlining the bumpers or altering the front of the cowling by the addition of two rounded humps do not consistently reduce drag at race velocities. 62,64,66 Full-scale wind tunnel test results.…”
Section: Bobsleigh Aerodynamic Optimization Strategies Noted From the Literaturementioning
confidence: 99%
“…50,64 The results of other studies have suggested that streamlining the bumpers or altering the front of the cowling by the addition of two rounded humps do not consistently reduce drag at race velocities. 62,64,66 Full-scale wind tunnel test results. As fractional scale model tests may omit construction details or provide only rough approximations of the bobsleigh or crew, the current research measured the aerodynamic drag of full-scale 2-and 4-person bobsleighs, with and without their crews, in a wind tunnel with simulated track walls positioned alongside the bobsleigh.…”
Section: Bobsleigh Aerodynamic Optimization Strategies Noted From the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Motallebi, Dabnichki, and Luck (2004) and Dabnichki and Avital (2006) conducted numerical simulations and wind tunnel experiments in order to improve single bobsleigh components as well as the posture of the bobsleigh crew. Winkler & Pernpeintner (2008) showed that the aerodynamic drag of a bobsleigh can be reduced by about 13% when applying the currently prevailing aerodynamic development process systematically including both computational and experimental tools.…”
Section: Introductionmentioning
confidence: 99%